Assessment of diffusion mobility for bcc phase of Ti–Al–Ni ternary system. (December 2020) - Wu, Qiaojun; Xu, Guanglong; Chang, Hui; Zhou, Lian; Cui, Yuwen
Abstract: The experimental diffusion coefficients of the Ti–Ni binary and Ti–Al–Ni ternary bcc phase were critically evaluated to assess the diffusion mobilities by the DICTRA-type phenomenological treatment. The calculated diffusion coefficient shows reasonable consistency with the diffusion coefficient extracted in the experiment, including the impurity and inter-diffusion coefficients in bcc Ti–Ni binary alloy and the main interdiffusion coefficient in bcc Ti–Al–Ni ternary alloy. The difference between the calculated and experimental ternary cross coefficients is within appropriate relative errors. The predicted composition profiles and diffusion paths reasonably represent the diffusion processes that occur in Ti–Ni binary and Ti–Al–Ni ternary diffusion couples, thereby validating the mobility database assessed in the present work.